2021
DOI: 10.1038/s41598-021-89166-8
|View full text |Cite|
|
Sign up to set email alerts
|

The gut microbiome is associated with brain structure and function in schizophrenia

Abstract: The effect of the gut microbiome on the central nervous system and its possible role in mental disorders have received increasing attention. However, knowledge about the relationship between the gut microbiome and brain structure and function is still very limited. Here, we used 16S rRNA sequencing with structural magnetic resonance imaging (sMRI) and resting-state functional (rs-fMRI) to investigate differences in fecal microbiota between 38 patients with schizophrenia (SZ) and 38 demographically matched norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 74 publications
1
46
0
1
Order By: Relevance
“…The presence of a distinct signature of gut microbiota components in patients affected by SCZ compared to HC is consistent with emerging evidence that molecular substrates of social, cognitive and emotional domains, known to be altered in SCZ, might be influenced by life-long microbiota–gut–brain axis signaling [ 41 ]. Indeed, a recent study showed that the higher relative abundance of genus Roseburia in SCZ patients, compared to HC, was negatively correlated with the regional homogeneity indexes of brain regions putatively involved in the pathophysiology of SCZ, such as the right superior temporal cortex, the left cuneus and the right medial temporal cortex [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a distinct signature of gut microbiota components in patients affected by SCZ compared to HC is consistent with emerging evidence that molecular substrates of social, cognitive and emotional domains, known to be altered in SCZ, might be influenced by life-long microbiota–gut–brain axis signaling [ 41 ]. Indeed, a recent study showed that the higher relative abundance of genus Roseburia in SCZ patients, compared to HC, was negatively correlated with the regional homogeneity indexes of brain regions putatively involved in the pathophysiology of SCZ, such as the right superior temporal cortex, the left cuneus and the right medial temporal cortex [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A smaller number of studies explore the predicted or actual functional alterations in microbial genes or metabolic pathways associated with these differences [41][42][43] . Changes in microbiota composition in psychosis and schizophrenia have been correlated with altered brain structure and function, altered immunity, altered metabolic pathways and symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that there are differences in the alpha and beta diversity in the microbial composition of people with psychosis and schizophrenia as compared with controls 21 , 23 , 40 . A smaller number of studies explore the predicted or actual functional alterations in microbial genes or metabolic pathways associated with these differences 41 43 . Changes in microbiota composition in psychosis and schizophrenia have been correlated with altered brain structure and function, altered immunity, altered metabolic pathways and symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a comparison of MRI images highlighted significant differences in both the volume of gray matter and the regional homogeneity amongst the two groups and higher amplitudes of low-frequency fluctuation in SZ patients. Finally, both changes in gray matter volume and regional homogeneity correlated with the diversity of the gut microbiota [ 171 ]. In a similar fashion, significant changes in the volume of the right middle frontal gyrus seem to be related to the specific composition of gut microbiota in SZ [ 163 ].…”
Section: Microbiota and Psychiatric Disordersmentioning
confidence: 99%